A simple, quick and contamination-free method for mass-multiplication of plant-beneficial microbes by small and marginal farmers using coconut water and rice gruel medium - GOPAL, MURALI; GUPTA, ALKA; HAMEED, K SHAHUL; CHANDRAMOHANAN, R; THOMAS, GEORGE V (The Indian Journal of Agricultural Sciences, 2019)
A simple method for mass-multiplication of microbial inoculants is reported which can empower small and marginal farmers, or group of farmers, to mass-multiply by themselves plant-beneficial microbial inoculants of bacterial plant growth promoting rhizobacteria (PGPR) such as Pseudomonas spp., Bacillus spp., free-living nitrogen-fixers like Beijerinckia spp., Azotobacter spp. and phosphate solubilizing bacteria like Bacillus megaterium) and fungal antagonists/entomopathogens such as Trichoderma spp., Metarhizium anisopliae) origin. The mass-multiplication medium is based on mixture of rice gruel and mature coconut water in a set ratio, along with microgram quantities of biochar filled in pressure cooker. The method yields contamination-free liquid bioinoculant containing sufficient viable cells (as per BIS norms) within 48 hr for bacteria and 4-7 days for fungal bioinoculant for immediate application (seed or seedling treatment and soil application) by the farmers. The method requires supply of proven contaminant-free and pure bioinoculant culture to farmers in pre-filled and stoppered syringes with long needle (5 or 10 ml volume) or pre-filled ink-filler from reliable and responsible agencies for mass-multiplication. The procedure requires little technical expertise and could to a large extent emancipate farmers from depending on bioinoculants available in agriculture stores in markets, which often suffer from contamination and below par viable inoculant population.